2015
DOI: 10.1039/c4nj01547a
|View full text |Cite
|
Sign up to set email alerts
|

Participation of non-aminoisobutyric acid (Aib) residues in the 310helical conformation of Aib-rich foldamers: a solid state study

Abstract: The solid state conformational preferences of a series of 2-aminoisobutyric acid (Aib) foldamers bearing a single N-terminal tertiary amino acid (Cbz-L-phenylalanine (Cbz-L-Phe)) have been investigated by X-ray crystallography. The type of b-turn present at the N-terminus and the global screw-sense preferences of the Aib foldamers were determined by analysis of intramolecular hydrogen-bonds and peptide torsion angles. The contrasting influence of a C-terminal ester or amide on the 3 10 helical conformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 92 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…The lower solubility of the racemates allowed crystals suitable for X-ray crystallography to be obtained for (rac)-1 (described previously 22 ) and (rac)-2; conditions to crystallise the enantiopure analogues were not found. Indeed, Huc and co-workers have used this increased propensity of racemic mixtures to crystallise to elucidate the structure of helical aromatic oligoamide foldamers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lower solubility of the racemates allowed crystals suitable for X-ray crystallography to be obtained for (rac)-1 (described previously 22 ) and (rac)-2; conditions to crystallise the enantiopure analogues were not found. Indeed, Huc and co-workers have used this increased propensity of racemic mixtures to crystallise to elucidate the structure of helical aromatic oligoamide foldamers.…”
mentioning
confidence: 99%
“…Columns of opposite screw sense interact in a side-by-side antiparallel fashion. The crystal structure of (rac)-1 was analogous, 22 with columns of oligomers of the same screw sense linked by intermolecular head-to-tail hydrogen bonds, but with intermolecular π-π interactions between antiparallel columns. 25 To assess the ability of (S)-1, (rac)-1, (S)-2 and (rac)-2 to transport small ions through bilayers, we chose the phospholipid vesicle-based 8-hydroxypyrenetrisulfonate (HPTS) assay, using EYPC/cholesterol (4 : 1) vesicles with an interior pH of 7.4 and an exterior pH of 8.4.…”
mentioning
confidence: 99%
“…One group of natural peptides do commonly adopt 3 10 -helical conformations; namely, the membrane-active fungal metabolites known as the peptaibols 16,17 . These short peptides are rich in -disubstituted amino acids, in particular α-aminoisobutyric acid (Aib, U) [18][19][20][21][22][23][24] , which favour tighter helical turns characteristic of 3 10 helices [25][26][27][28] . However, the formation of 3 10 helices appears to fall off with lengths >9 residues, where -helix formation becomes favoured 29 .…”
Section: Kumar Et Al De Novo 3 10 -Helical Bundlesmentioning
confidence: 99%
“…Studies in solution have demonstrated that Aib foldamers weakly self‐associate in chloroform solution, a solvent that is often assumed to mimic the membrane environment [6,26] . X‐ray investigations on the racemic mixtures of both 1 and 2 showed that in the solid state the peptides adopt a 3 10 helical conformation [18,27] . 8‐Hydroxypyrenetrisulfonate (HPTS) studies of the ionophoric activity of the peptide 1 in EYPC/cholesterol vesicles showed that at concentrations of 60 μM (25 : 2 lipid/peptide), the peptide allowed the leakage of ions and dye through the membrane without disrupting it.…”
Section: Introductionmentioning
confidence: 99%